ANALISIS SUSTAINABILITY CREATIVE TOURISM DI KOTA MALANG - Dullah, Mohammad (Universitas Ciputra Surabaya, 2024)
The city of Malang, which has many kinds of creative tourism in it, needs to study carefully how the sustainability of the industry will be in the future, the data shows a decrease in tourist visits, which was initially caused by a pandemic, but when tourism began to reopen, public interest was not as big as before. This research was carried out in Tridi Village and Colorful Village in Malang City which was carried out with qualitative research. The results of this study indicate that 1) Economic, social and environmental development in Tridi Village develops in accordance with the views of the local community, where the existing social phenomena are not fully supportive but can adjust because there is no direct involvement with village development because they are represented by artists. 2) Economic, social and environmental development in Kampung Warna-warni develops in accordance with the views and views of the local community, where the social phenomena that exist there are in line with the development of a community that is friendly and harmonious and prioritizes kinship, so that the results and development there can be enjoyed together by citizens and for citizens as well.